FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA MINAT TERHADAP KONTRASEPSI INTRAUTERINE DEVICE DI BPM KERTAPATI - Ostradela, Maria; Minarti, Minarti (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Intra Uterine Device is a contraceptive that is placed in a vacuum to block fertility and makes it difficult for the eggs to implant in the uterus. Globally, users of modern contraception have increased from 54% in 1990 to 57.4% in 2014.of this study was to determine the factors associated with the low interest in Intarauterine Device contraception in BPM Sundari Kertapati in 2019. This study used an analytical survey research method with a cross sectional research design. Sampling was carried out using accidental sampling obtained as many as 81 acceptors. The instrument used was a questionnaire. by using the chi square test analysis showed the results there was a significant relationship between the role of health workers to the low interest of IUDs with p = 0,000, there was a significant relationship between maternal knowledge of the low interest of IUDs with p = 0,000, there was a significant relationship between encouragement husband's low interest in IUD with p = 0,000. It is hoped that health workers will improve people's understanding by approaching and changing people's attitudes with false myths about IUDs. Improve acceptor knowledge education about the effectiveness, advantages and disadvantages of IUD contraception. Educating the husband to support his wife using an IUD with an approach, counseling and socialization about IUD contraception.Keyword : Use of Intrauterine Devices, the Role of Health Officers, Mother's Knowledge and Husband's Encouragement.